Erosion performance of natural fiber reinforced vinyl ester hybrid composites: Effect of layering sequences. (2022) - Muthusamy, Anandha Raja; Thiagamani, Senthil Muthu Kumar; Krishnaswamy, Senthilkumar; Muthukumar, Chandrasekar; Pulikkalparambil, Harikrishnan; Subramanian, Jeyanthi; Madasamy, Naganandhan
Abstract: The purpose of this study is to investigate on erosion performance of hybrid polymer composites under various parameters such as impingement angle and time. The vinyl ester composites used for the erosion tests were prepared by layering sequences of Jute (J), Kenaf (K), and Banana (B) fibres. Three composites with single fibres and three hybrid composites were prepared to understand the influence of layering sequence. The erosion performance of the composites was carried out by an Air jet erosion analyzer. In this study, different impingement angles of 90° and 60° for a period of 2, 4, and 6 min were exploited. Alumina particles were used as the erodent material at an erodent discharge rate of 3.3 g/m and the impact velocity of 72 m/s. The eroded samples were examined using the optical microscope to analyze the effect of erosion in the J/K/B vinyl ester composites. Finally, the erosion performance of the J/K/B reinforced vinyl ester hybrid composites was analyzed by comparing the reduction in weight of composites after erosion to initial weight of the composite materials.